Intrinsically Stretchable and Self-Healing Electroconductive Composites Based on Supramolecular Organic Polymer Embedded with Copper Microparticles - Yeasmin, Rubaya; Duy, Le Thai; Han, Seungik; Seo, Hyungtak (Advanced Electronic Materials, 2020)
Integration of electrical conductivity, stretchability, and self-healing properties of electronic material is a promising way to meet the criteria for developing next-generation technologies ranging from ordinary sustainable electronics to high-tech human–machine interfaces. To this particular purpose, a cost-effective composite material having simultaneous functionalities of electrical conductivity, stretchability, and self-healability based on supramolecular organic polymer and copper microparticles is presented. The composite can be mass-produced via the sol–gel method and is tunable by adjusting the copper loading. Electrical and mechanical characterizations show that the composite material owns not only a high stretchability (≥120%) but also an excellent self-healability at ambient conditions within 5 min. The healing efficiency is about 90% for its mechanical property and almost 100% for its electrical properties. Besides, the electrical properties are found in the range of semiconductors that can be restored upon five cutting–healing cycles. One-step further, the developed material is utilized to fabricate a wearable strain sensor. Also, real-time human motion detection is demonstrated using the fabricated sensor. These results exhibit the potential of the material for developing self-healing electronic devices and show promising directions in the field of wearable and sustainable electronics, human–machine interfaces.
Keywords: Copper microparticles; Electrical conductivity; Electro-conductive composites; Generation technologies; Human motion detection; Mechanical characterizations; Self-healing properties; Sustainable electronics; copper microparticles; electroconductive materials; self-healing devices; stretchable materials; supramolecular organic polymers